FEASIBILTY STUDY OF POROUS MEMBRANE TECHNOLOGY TO REDUCE SILICA SCALING PROBLEM OF INJECTED WATER IN DIENG GEOTHERMAL FIELD - Reynaldi Khrisna Wardana, Agung
Production problems in gothermal power plant industries tend to happens almost in every geothermal field in Indonesia, including Dieng geothermal field. Among a number of production problem types, silica scaling is the most significant to reduce the production flowrate of the geothermal fluids. Decreasing flowrate of the geothermal fluids could leads to difficulty of maintaining the installed capacity of geothermal power plants. High cost of maintenance to resolves silica scaling problem then leads to increasing number of study and research which aims to produce new methods that could prevent silica scaling from happening. One of the prevention methods is to separate the silica content in the geothermal fluids. But in a certain cases, the silica particle in the geothermal fluids which would be reinjected back to the reservoir still could created silica scaling problem. This is become the basis to conduct further research which could separated most of the silica particle from the geothermal fluids so the silica scaling could be prevented. Porous membrane technology has basic principle to separate dissolved solids in some solvent fluid based on particle diameter size. With that principle, porous membrane technology make it possible to separate most of the silica particle in the geothermal fluids by using such a lower cost. Porous membrane technology has been proven to be technically and economically feasible in order to reduce the silica scaling potential. Porous membrane capability to reduce silica concentration in the water indicated the technical feasibility. Where the cost of the porous membrane technology applied would be ranging from USD 73,000-146,000 a year, porous membrane could decrease the silica scaling potential by the SSI value to 0.33 and at the same time silica would be separated at the surface and would not followed the reinjected fluid to the reservoir through reinjection well. The separated silica by the porous membrane also could be used as side benefits of the geothermal power plants, with the average production rate of silica at 13,288 kg a day, which is equivalent to USD 484,355-1,937,055 a year.